2008
DOI: 10.1007/s10682-008-9266-0
|View full text |Cite
|
Sign up to set email alerts
|

Positive genetic correlations between life-history traits and death-feigning behavior in adzuki bean beetle (Callosobruchus chinensis)

Abstract: Usually, several traits in organisms are genetically linked with each other; thus, correlated responses to selection are generally observed. Anti-predator behaviors may be genetically correlated with other traits such as life-history. We compared the life-history traits of individuals derived from two regimes artificially selected for the duration of death feigning in the adzuki bean beetle, Callosobruchus chinensis. The two-way selected regimes include the L-lines with stronger intensity (longer duration and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…In the present study, the duration of death‐feigning is positively correlated with female life span and male weight, although the correlation is not genetic but phenotypic. These results are consistent with previous studies on other beetle species at phenotypic levels (Hozumi & Miyatake, 2005; Ohno & Miyatake, 2007; Miyatake et al , 2008; Nakayama & Miyatake, 2009, 2010a, b, c). Specifically, the negative genetic correlation between death‐feigning and activity level could be responsible for the positive genetic correlations between death‐feigning and life‐history traits such as reproductive effort and life span.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the duration of death‐feigning is positively correlated with female life span and male weight, although the correlation is not genetic but phenotypic. These results are consistent with previous studies on other beetle species at phenotypic levels (Hozumi & Miyatake, 2005; Ohno & Miyatake, 2007; Miyatake et al , 2008; Nakayama & Miyatake, 2009, 2010a, b, c). Specifically, the negative genetic correlation between death‐feigning and activity level could be responsible for the positive genetic correlations between death‐feigning and life‐history traits such as reproductive effort and life span.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic correlations between the frequency and duration of death‐feigning and life‐history traits such as life span, emergence rate, body size, reproductive efforts and locomotor activities are documented in other beetle species, including the adzuki bean beetle Callosobruchus chinensis and red flour beetle Tribolium castaneum (Hozumi & Miyatake, 2005; Ohno & Miyatake, 2007; Miyatake et al , 2008; Nakayama & Miyatake, 2009, 2010a, b, c). In the present study, the duration of death‐feigning is positively correlated with female life span and male weight, although the correlation is not genetic but phenotypic.…”
Section: Discussionmentioning
confidence: 99%
“…We supported some previous studies by showing that rapid interruption in activity by flicking the substrate was associated with longer periods of immobility in T. molitor (Nakayama and Miyatake 2010;Nakayama et al 2012;Nishi et al 2010;Nakayama and Miyatake 2009;Krams et al submitted). The results obtained within and between contexts suggests a behavioral syndrome in anti-predator behavior of T. molitor, where behavioral correlations arise as a consequence of individual variation in two or more behaviors (e.g., Bell et al 2009;Kortet and Hedrick 2007;Réale et al 2010a, b;Sih et al 2004).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, Nakayama and Miyatake (2009) have reported a positive genetic correlation between death feigning and life-history traits in the adzuki bean beetle, Callosobruchus chinensis (Linn). They found that individuals with a genetically stronger intensity of death feigning have greater longevity, higher rates of emergence and a tendency to develop faster, and lay larger eggs than individuals exhibiting a weaker intensity of death feigning.…”
Section: Discussionmentioning
confidence: 99%